Optimization of titanium dioxide production process for photocatalytic degradation of 2,4 dichlorophenoxyacetic acid - Duranoglu, Dilek; Yilmaz, Yeliz (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2024)
In this study, photocatalytic degradation of 2,4 Dichlorophenoxyacetic acid (2,4D), one of the the most used pesticide, was investigated by TiO2 photocatalyst produced by sol-gel method. Three different parameters (Titanium isopropoxide (TIP) amount, HNO3 concentration and aging time) were investigated and modelled by applying Box Behnken Experimental Design method for optimum TiO2 synthesis. Photocatalyst production process was optimized by examining the 2,4D photocatalytic degradation rate of TiO2 photocatalysts produced under different process conditions. TiO2 samples, which were synthesized with the optimum conditions, were characterized by XRD (X-ray Diffraction), SEM (Scanning Electron Microscope), zeta potential, particle size analysis, and also compared with commercial Degussa P25 TiO2 photocatalyst. 2,4D photocatalytic degradation rate was determined as 0.0084 min-1 for the optimum condition 1 (TIP amount: 24.08 mL, HNO3 concentration: 3.53 M, aging time: 2.29 hours) and 0.0085 min-1 for the optimum condition 2 (TIP amount:10.33 mL, HNO3 concentration: 0 M and aging time: 19.51 hours). The amount of used acid was reduced to zero or the aging time was reduced to the lowest value (2.29 h) by optimizing the TiO2 production parameters via experimental design methodology, hence, a very high photocatalytic efficiency was obtained.
Keywords: Photocatalytic degradation; 2; 4 dichlorophenoxyacetic acid; titanium dioxide; Box-Behnken experimental design; optimization; 2,4-DICHLOROPHENOXYACETIC ACID; HETEROGENEOUS PHOTOCATALYSIS; TIO2 NANOPARTICLES; WATER-TREATMENT; REMOVAL; Engineering